2013
DOI: 10.1002/ppap.201300035
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation and Heme Degradation of Horseradish Peroxidase Induced by Discharge Plasma

Abstract: The effects of non‐thermal plasma at the argon gas–solution interface on horseradish peroxidase (HRP), a classical heme‐containing protein, were assessed quantitatively. Evidence from spectroscopic approaches showed that enzymatic activity together with the contents of heme and iron in HRP decreased dramatically and concomitantly upon plasma treatment. The plasma induced both long‐ and short‐lived reactive species which inactivated HRP in the solution. In particular, hydrogen peroxide broke the heme prosthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 67 publications
6
26
0
Order By: Relevance
“…This also correlates with previous work by other authors, in which a similar trend after plasma treatment was also observed3233. However, the fluorescence analysis shows the degradation of the heme group in protein; the hemes are non-fluorescent, but during the heme degradation, the fluorescent porphyrin degradation product yield increased15192021. Comparing the percentage of α-helical decreases between the O 2 and N 2 admixtures at all mixture ratios (O.2%, 0.3%, and 0.4%) and at all treatment times (1, 2, and 4 min), we found that the α-helical decreases more for O 2 admixtures than for N 2 admixtures.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This also correlates with previous work by other authors, in which a similar trend after plasma treatment was also observed3233. However, the fluorescence analysis shows the degradation of the heme group in protein; the hemes are non-fluorescent, but during the heme degradation, the fluorescent porphyrin degradation product yield increased15192021. Comparing the percentage of α-helical decreases between the O 2 and N 2 admixtures at all mixture ratios (O.2%, 0.3%, and 0.4%) and at all treatment times (1, 2, and 4 min), we found that the α-helical decreases more for O 2 admixtures than for N 2 admixtures.…”
Section: Discussionsupporting
confidence: 91%
“…However, the fluorescence intensity decreases as the admixture ratios increase, while no significant difference in intensity was observed for the 1 and 2 min treatments for both proteins (Hb and Mb). In the previous reports, the researchers observed that the OH/H 2 O 2 radicals are mainly responsible for the heme degradation192021. Therefore, for the Ar gas plasma, the OH and H 2 O 2 concentrations increase as the treatment time increases, so that the degradation also increases.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…For assessment of the integrity of the heme cofactor, absorption spectra were recorded for the protein samples that were tested for activity (inset of Figure ). In congruence with previous reports, the absorption of the Soret band declined after plasma exposure, indicating that the heme was modified. Heme has been shown to be attacked by ROS, for example, O 2 .− radicals and H 2 O 2 , both of which represent major components of the discharge and the treated liquid.…”
Section: Resultssupporting
confidence: 92%
“…Inactivation of enzymes with the plasma source used here has been shown before, for example, for RNase A, which was fully inactivated after 5 min treatment . Activity loss of heme‐containing proteins, and specifically HRP, has also been studied, albeit not with the plasma device used here. Upon treatment with an argon discharge, HRP was fully inactivated within 30 min.…”
Section: Resultsmentioning
confidence: 95%